2006
DOI: 10.1007/bf03325921
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary assessment of heavy metals levels of soils of an oil field in the Niger Delta, Nigeria

Abstract: A BS T RA C T:This communication presents the results of preliminary investigation of the characteristic levels of heavy metals in surface soils of an oilfield in the Niger Delta. The results indicate higher concentration of the following metals: Cd, Pb, Cu; Ni, Zn, Cr, Mn and Hg in soils around the gas plant than the pipeline areas. There is a significant temporal and spatial variation in the concentrations of the heavy metals. Samples collected during the wet season showed lower concentrations of heavy metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
32
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 17 publications
11
32
3
1
Order By: Relevance
“…Lower values during the month of August may be due to more ionic dilution within the water aquifer because of increase rainfall and is in agreement with the findings of Iwegbue, Egobuez and Opuene [55] within the Niger Delta area, they also added that the sampling period variations in the levels of the heavy metals could be attributed to the difference in individual metals solubility, pH, leaching by acid rain during the wet season and topography of the area. Toxic metals trend in groundwater samples is in the order Cd (0.106 ± 0.009)>Pb (0.061 0.001)>Ni (0.048 ± 0.023)>Co (0.004 ± 0.001) for the month of June (first sampling), and Ni (0.098 ± 0.168)>Pb (0.088 ± 0.085)>Cd (0.082 ± 0.058)>Co (0.011 ± 0.008) for the month of August (second sampling) ( Table 7).…”
Section: Month Of Collectionsupporting
confidence: 86%
“…Lower values during the month of August may be due to more ionic dilution within the water aquifer because of increase rainfall and is in agreement with the findings of Iwegbue, Egobuez and Opuene [55] within the Niger Delta area, they also added that the sampling period variations in the levels of the heavy metals could be attributed to the difference in individual metals solubility, pH, leaching by acid rain during the wet season and topography of the area. Toxic metals trend in groundwater samples is in the order Cd (0.106 ± 0.009)>Pb (0.061 0.001)>Ni (0.048 ± 0.023)>Co (0.004 ± 0.001) for the month of June (first sampling), and Ni (0.098 ± 0.168)>Pb (0.088 ± 0.085)>Cd (0.082 ± 0.058)>Co (0.011 ± 0.008) for the month of August (second sampling) ( Table 7).…”
Section: Month Of Collectionsupporting
confidence: 86%
“…Relatively low amounts of the metals are found in the readily available (F 1 and F 2 ) and Fe -Mn oxides fractions as compared to the impacted sites. This suggests that high amounts of metals found in F 1 , F 2 and F 3 fractions at the impacted sites resulted from anthropogenic inputs, since exogenous metals are more weakly bound to the soil matrix and therefore are more readily released (Abollino et al, 2002;Iwegbue et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…William (2001) also observed that As concentrations in mine waters increased in the wet season compared to the dry season. Such seasonal variation in the concentration of As could be attributed to differences in individual As solubility, pH, and leaching by acidic rain during the wet season (Iwegbue, Egobueze, & Opuene, 2006). Similarly, in the wet season, As concentration in Athi River was significantly higher than in Ngong.…”
Section: Heavy Metal Concentration In Irrigation Watermentioning
confidence: 97%
“…In general, heavy metal concentrations of Co, Cr, Cu, and Ni were significantly higher in the dry season compared to the wet season. Action of water dilution could be the main reason for the reduction in heavy metal concentrations during the wet season (with the exception of As) (Iwegbue et al, 2006). While boron is essential for plant development (Jacob, 2007) The first principal component, D1, shows that 55.87 percent of the total variance is highly loaded by B, Cu, Co, and Ni, which were present in Ngong (figure 3).…”
Section: Heavy Metal Concentration In Irrigation Watermentioning
confidence: 99%